TIGIT signaling and its influence on T cell metabolism and immune cell function in the tumor microenvironment - Jantz-Naeem, Nouria; Böttcher-Loschinski, Romy; Borucki, Katrin; Mitchell-Flack, Marisa; Böttcher, Martin; Schraven, Burkhart; Mougiakakos, Dimitrios; Kahlfuss, Sascha (Frontiers in Oncology, 2023)
One of the key challenges for successful cancer therapy is the capacity of tumors to evade immune surveillance. Tumor immune evasion can be accomplished through the induction of T cell exhaustion via the activation of various immune checkpoint molecules. The most prominent examples of immune checkpoints are PD-1 and CTLA-4. Meanwhile, several other immune checkpoint molecules have since been identified. One of these is the T cell immunoglobulin and ITIM domain (TIGIT), which was first described in 2009. Interestingly, many studies have established a synergistic reciprocity between TIGIT and PD-1. TIGIT has also been described to interfere with the energy metabolism of T cells and thereby affect adaptive anti-tumor immunity. In this context, recent studies have reported a link between TIGIT and the hypoxia-inducible factor 1- (HIF1-α), a master transcription factor sensing hypoxia in several tissues including tumors that among others regulates the expression of metabolically relevant genes. Furthermore, distinct cancer types were shown to inhibit glucose uptake and effector function by inducing TIGIT expression in CD8+ T cells, resulting in an impaired anti-tumor immunity. In addition, TIGIT was associated with adenosine receptor signaling in T cells and the kynurenine pathway in tumor cells, both altering the tumor microenvironment and T cell-mediated immunity against tumors. Here, we review the most recent literature on the reciprocal interaction of TIGIT and T cell metabolism and specifically how TIGIT affects anti-tumor immunity. We believe understanding this interaction may pave the way for improved immunotherapy to treat cancer.